Analysis of Determinants of Foreign Exchange Reserves in ASEAN-5 Countries - Pebriyanti, Intan; Khoirudin, Rifki (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
Foreign exchange reserves represent a nation's holdings of foreign currencies or currency equivalents, managed by its central monetary authority, and utilized in global transactions and engagements. This research aims to analyze the influence of inflation, Foreign direct investment, Exchange rate, economic growth and exports to the level of foreign exchange reserves in ASEAN-5 countries 2000-2022. This study relies on secondary data sourced from the World Bank's official website. The analytical methodology involves employing a panel data regression technique known as the Fixed Effect Model (FEM) alongside the analysis tools provided by StataMP17. The results of data processing show that partially each independent variable is inflation, Foreign direct investment, Exchange rate, Economic growth demonstrates a notable negative impact on Foreign Exchange Reserves within ASEAN-5 nations, with statistical significance. Conversely, the independent variable Exports exhibits a positive and significant correlation with Foreign Exchange Reserves across ASEAN-5 countries